Letter from W.T.A. Foot of London Central Strike Committee (NUR) to General Council, n.d., Re: Need for strike bulletin
"Letter from W.T.A. Foot of London Central Strike Committee (NUR) to General Council, n.d., Re: Need for strike bulletin" [g0726001.jpg], n.d., National Union of Railwaymen TUC Organisation